Sorption Kinetics, Isotherm Studies and Mechanism of Removal of Organic and Inorganic by Adsorption onto Renewable Biomineral - Detho, Amir; Memon, Asif Ali; Memon, Aftab Hameed; Almohana, Abdulaziz Ibrahim; Daud, Zawawi; Rosli, Mohd Arif (2023)
Natural material, agricultural waste, and industrial waste are locally accessible resources that are utilized as environment-friendly and inexpensive sorbent. The natural abundance source like green waste mussel shell (GWMS) adsorbent makes them an advantageous basic sorbent material to produce inexpensive water treatment adsorbent. This study addresses the evaluation of GWMS as an efcient sorbent material to minimize the utilization of traditional adsorbents namely activated carbon (AC) and zeolite (ZEO) for removing pollutants from leachate. COD and ammoniacal nitrogen (NH3–N) were identifed as the two problematic parameters in landfll leachate. Batch adsorption experiments were performed with 100 mL of prepared leachate solution in 2.5 g, 7.5 g, and 12.5 g dosages. The leachate solution was shaken in an incubator for 2 h at 200 rpm shaking speed and pH 7. The GWMS dosage at 7.5 g illustrated that the removal percentage of COD is 71% and that of NH3–N is 47%. The adsorption capacity related to the complete monolayer coverage of saturated molecules shows that the maximum adsorption capacity of COD is 47.39 mg g−1 and that of NH3–N is 26.18 mg g−1. Langmuir and Freundlich values are better described by Langmuir than Freundlich based on R2 values for COD > NH3–N where 0.9941>0.9891. The R2 values for COD > NH3–N for the linear plot of the pseudo-second-order were 0.9997>0.9763, respectively